Kinerja Aparatur Sipil Negara Dalam Pengurusan Tanda Pendaftaran Lembaga Kesejahteraan Sosial Pada Bidang Pemberdayaan Sosial Dinas Sosial Kota Palu - Syukur, M; Srifridayanti, Srifridayanti; Suhartini, Eka Shitta (Sekolah Tinggi Ilmu Administrasi (STIA) Pembangunan Palu, 2024)
This study is to determine the performance of the State Civil Apparatus in managing the Registration Certificate of the Social Welfare Institution in the Social Empowerment Division of the Palu City Social Service. The basis of research used is qualitative and descriptive research type. The type of data uses primary data and secondary data. Data collection techniques, conducted through observation, interviews, and documentation. Informant withdrawal technique using purposive. The theory used is Robbins' theory which consists of 3 (three) aspects, namely motivation, ability and opportunity. From the results of the research conducted, it is known that the Performance of the State Civil Apparatus in the Management of Registration Signs of Social Welfare Institutions in the Social Empowerment Division of the Social Service of Palu City is relatively ineffective and maximum. from the aspect of motivation, it is found that employee motivation formed or driven from within themselves tends to be very low. In the aspect of the ability of Mastery of work by employees in the Social Empowerment Sector is quite good, it can be seen from the job responsibilities given to each employee, carried out well. Meanwhile, the knowledge possessed can be said to be very good because it is placed according to their abilities and educational background of employees. Furthermore, in the aspect of opportunity, it is concluded that from the past until now all employees in the Social Empowerment Sector have been given the same opportunity in carrying out their duties